The Implementation of Zakat Funds in Disaster Risk Reduction in Indonesia: Evidence in BAZNAS Disaster Resilient Village - Edo Segara Gustanto; Anton Priyo Nugroho (Universitas Ahmad Dahlan, 2025)
Introduction to The Problem: Indonesia is a country prone to natural disasters, and the need for effective disaster risk reduction strategies is increasingly urgent. At the same time, zakat as a form of Islamic philanthropy remains underutilized in structured disaster mitigation efforts. Purpose/Objective Study: This study aims to examine how zakat funds are implemented in the Disaster Resilient Village (Katana) program and assess their effectiveness in reducing disaster risks through community empowerment and infrastructure development. Design/Methodology/Approach: The research employs a qualitative descriptive approach using data from case studies, institutional reports, and previous literature. Data collection includes interviews and documentation from relevant zakat institutions and disaster mitigation actors. Findings: The findings reveal that zakat funds, when properly managed and integrated, can significantly contribute to disaster resilience by supporting economic empowerment, infrastructure development, and preparedness efforts. Challenges include limited coordination between government and private zakat institutions. The study recommends stronger collaboration across stakeholders and greater public education to enhance understanding of zakat’s potential in disaster mitigation.